Utilising Tshivenḓa Scientific Language Register for Teaching Electric Circuits - Ntuli, Thuli Gladys; Madavha, Mpho Kenneth; Mudau, Awelani Victor (Research in Social Sciences and Technology, 2024)
Teaching physical sciences in English as the Language of Learning and Teaching (LOLT) has presented numerous challenges, particularly for learners who are not proficient in the language. The South African government is increasingly considering the use of indigenous languages as the medium of instruction for subjects such as physical sciences, sparking debates regarding the effectiveness of indigenous languages in teaching and learning. This study aimed to explore stakeholders' perceptions regarding the use of Tshivenḓa scientific language for the concept of electricity. Utilizing qualitative interpretative case study methodology, the researcher conducted interviews with two grade 10 teachers, three parents, and two groups of grade 10 learners from selected schools to investigate their views on using Tshivenḓa scientific language register to teach physical sciences. The findings indicate that stakeholders view the adoption of scientific language registers in Tshivenḓa as a positive initiative. They believe it will provide learners who struggle to understand physical sciences when taught in English with an opportunity to learn effectively in a language they are familiar with. Therefore, the study recommends expanding the development of scientific registers in Tshivenḓa to cover other topics in physical sciences.